Pengaruh Profesionalisme, Pengetahuan Mendeteksi Kekeliruan, dan Etika Profesi Terhadap Pertimbangan Tingkat Materialitas Akuntan Publik - Arleen Herawaty; Yulius Kurnia Susanto (Jurnal Akuntansi dan Auditing Indonesia, 2009)
To defence trusting from client and user of financial statement, public accountant strives to have adequacy competent. The competents are professionalism, auditor’s knowledge for errors and public accountants’ judgement of materiality level. The aim of this study was to get emperical evidence about the effect of professionalism, auditor’s knowledge for errors and professional ethics on public accountants’ judgement of materiality level in the auditing process of financial statements. Data were obtained by survey questionnaires, which were completed by accountants who work at Registered Public Accountants, started from senior up to partner level. Data were analyzed using multiple regression analysis. The result of this study showed that professionalism, auditor’s knowledge for errors and professional ethics have significant and positive influence to public accountants’ judgment of materiality level in auditing process of financial statements.Keywords: Professionalism, auditor’s knowledge for errors, professional ethics and public accountants’judgment of materiality level